ANALISIS HUB UNGAN KARAKTERISTIK PERAWAT TERHADAP PERSEPSI KEMUDAHAN DAN KEMANFAATAN PENGGUNAAN SISTEM ELECTRONIC HEALTH RECORD (EHR) DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Sami Kandha Dipura; Ramadin Ramadin (MIKKI (Majalah Ilmu Keperawatan dan Kesehatan Indonesia), 2018)
ABSTRACTBeneﬁ ts of implementing Electronic Health Record (EHR) relating to its purpose to improve the quality of health services, must also be parallel with an evaluation of its implementation, there is no standard as a reference in evaluating of an EHR system that is why many researches in EHR evaluation uses various methods, while in this study the EHR evaluation was conducted by adopting the Technology Acceptance Model (TAM) which consisted of perceptions of convenience and perceived usefulness in which to be assessed from various nurse characteristics such as age, gender, education and tenure. To achieve this goal, the researchers analyzed nurse characteristics of themselves as a basis on their perceptions (the ease of use and the usefulnes) in using the EHR system in PKU Muhammadiyah Yogyakarta Hospital, as one of the hospitals that have implemented EHR since 2005. The research design was a cross sectional with descriptive-evaluative, and a quantitative approach to measure the phenomenon encountered, with sample of 100 nurses out of 198 in total number nurses, that was conducted in March till May 2017. The results showed that there were no signiﬁ cant differences between nurse characteristics such as age, sex, education and tenure toward the perceived ease of use and the perceived of usefulness, in the already implemented EHR system in PKU Muhammadiyah Hospital in Yogyakarta. This ﬁ nding provided a positive as well as a negative meanings, positive meaning mean that the EHR system applied had been successfully implemented and accepted by the user whatever nurse characteristics, or viceversa in negative meaning mean that the EHR system that was applied was not complex in terms of utilizing the latest technology, this impacted on perception of the EHR system which showed the same score for all nurse characteristics regardless of their age, education, gender or tenure.